Discovering English Pre-Service Teachers' Perception of ICT-Based Media Used in ELT - Rivaldo, Muhammad Frederick; Sari, Senorica Yulia (Journal of English Language Teaching, 2025)
This study aimed to explore the perceptions of EFL pre service teachers regarding the use of ICT-based media as a teaching tool. A quantitative, descriptive research design was employed, using a Likert scale questionnaire consisting of 27 positively worded statements across four indicators: interest, concern, object, and environment. Each item was rated on a four-point scale (1 = strongly disagree to 4 = strongly agree). The sample included 106 pre-service teachers. Descriptive statistical analysis was conducted to determine the percentage scores for each indicator. The findings indicate that pre-service teachers generally hold positive perceptions of ICT based media in English language teaching. The highest mean score was in the "interest" indicator (3.43), categorized as very positive. The "object" aspect, referring to the use of ICT tools in teaching, also received a high mean score (3.38). The "environment" and "concern" indicators scored 3.27 and 3.10, respectively, both falling into the positive category. Overall, the results suggest that EFL pre service teachers view ICT based media as a beneficial and effective tool for teaching English.